IMPLEMENTATION OF ISLAMIC RELIGIOUS EXTENSION PROGRAM WITH YANBU'A METHOD IN THE NEW NORMAL ERA - Solihin Solihin; Nur Azizah (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2021)
The process of learning the Qur'an uses the old method which is considered difficult so that a new method is needed at TPQ Raudlatun Nasir so that the Islamic Religious Counselor of KUA Kedungbanteng together with all elements of Keniten Village, Kedungbanteng District make a new breakthrough in reading the Qur'an. The aim is to analyze the implementation of the Islamic religious education program at the Office of Religious Affairs (KUA) of Kedungbanteng District using the Yanbu'a method carried out by the Kedungbanteng KUA Extension Team. The results of this study indicate that the religious counseling program from the KUA Kedungbanteng, namely tutoring the Qur'an at TPQ Raudlatun Nasir using the Yanbu'a method, shows awareness and increased interest in learning to read the Qur'an using the Yanbu'a method. The supporting factors for the success of this program are influenced by the spirit of the Islamic religious instructor KUA Kedungbanteng District to advise and remind each other to do good and bad deeds in learning the Qur'an and public acceptance of the presence of Islamic religious instructors while accompanying TPQ Raudlatun Nasir during the new normal era.Keywords: Islamic Religious Counseling, Yanbu'a . Method